Prevalence of attention deficit hyperactivity disorder in an urban school of a developing country - Yewatkar, Durgesh V.; Pande, Dwarika Prasad; Bangde, Laxmipriya A.; Joshi, Tanushree (International Journal of Research in Medical Sciences, 2017)
Background: Attention deficit hyperactivity disorder (ADHD) is one of the most common neuro-psychiatric disorder in children. Hence, the prevalence of ADHD and its types in school children as a community based survey in an urban Indian region was assessed in this study. Methods: A cross-sectional study conducted in an urban English medium school. Children studying in sixth to tenth standard were recruited for the study. DSM-IV based ADHD questionnaire was put forth to parents and teachers. Demographic details, information about their family and school environment were collected from students. Their performance in last year final examination in school was assessed from school records. Statistical analysis was carried out with either Fisher’s exact probability test or Chi-square test. Results: A total of 32/500 (6.4%) children have been diagnosed to have ADHD from the response from parents. Of the 32 ADHD children, 25 (78.1%) were boys and 7 (21.9%) were girls. A majority [22 (68.8%)] were of inattentive type, 2 (6.3%) were hyperactive and 8 (25%) had combined type of ADHD. An unfavourable family environment has been found to be significantly associated with ADHD (P < 0.001). A statistically significant difference (P<0.0001) in school performance was noted in children with ADHD. ADHD children were found to have unfavourable peer relationship more likely than non-ADHD children both in school [25/32 (78.1%)] and at home [16/32 (50%)]. Conclusions: We found prevalence of ADHD to be 6.4% in an urban English medium school necessitating an early identification through mass screening programmes and directing appropriate interventions.